As reformas graduais da sociedade aberta de Popper - Almeida, Pedro Augusto Ciola de (2017)
The philosophers are insightful in capturing the great changes in mainly of human activities such as economy, policy, science, religion and ethic. It doesn't only change the world we live but also man comprehension about themselves and the place ourselves occupy in universe. It doesn't mean the philosopher will make a well-succeeded reflection about the problems which cross his way. In fact, it happens the opposite: we commit more mistakes than right perceptions. Because of this according to Popper we must be criticals including about ourselves. In addition, Popper realized the scientifical revolution that would be with the coming of Einstein's science and he produced a new pattern of limit between science and non-science with the falsificacionism as well as he reinterpreted the value of scientifical and philosofical knowledge from a non-optimistic epistemology. On political philosophy, Popper inspired himself on Scandinavian counries and United Kingdom to build what he called openned society which means a tolerable society, not ready and over but under reformation on gradually and full time. Identifying the gradual and slow reformations of the open society is the thesis of this dissertation